DESCRPTION OF TRIGONOMETRY PROBLEM SOLVING ABILITIES BASEN ON PERSONALITY TYPE AND MATHEMATICS LEARNING ANXIETY LEVELS OF THE STUDENT AT SMAN 6 MAKASSAR - Kasriana Kasriana; Rasid Ode (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study aimed to describe the high school students in solving problems based on personality types and levels of anxiety learn. The subjects were students of class X SMA 6 Makassar with stratified sampling.The results showed that: (1) in understanding the problem, studentstype of idealist  high anxiety levels did not write sufficient conditions and a necessary condition; (2) in planning problem solving, students are able to determine the relevant information to solve problems; (3) in carrying out the plan of solving the problem, the students do the problems in accordance with the troubleshooting steps. (1) in understanding the problem, subject idealist with low anxiety level is able to write what is known and what is being asked; (2) in planning problem solving, students are able to find connections between things that are known and things that were asked; (3) in carrying out the plan of solving the problem, the students use the steps that have been prepared. (1) in understanding the problem, students rational types with high anxiety levels did not write sufficient conditions and a necessary condition; (2) in planning problem solving, students are able to receive the information used to determine the formula. (3) in carrying out the plan of solving the problem, students are able to solve problems that have been designed in accordance strategy. (1) in understanding the problem, students rational types with low anxiety levels did not write sufficient conditions and a necessary condition; (2) in planning problem solving, students are able to associate the information on the matter; (3) in carrying out the plan of solving the problem, students are able to use the steps correctly